Malay magic being an introduction to the folklore and popular religion of the Malay Peninsula - Skeat, Walter William (MBRAS reprint, 2005)
A century has passed since Walter Skeat wrote his 'Malay Magic' as an ethnographic record of rural Malay life in Selangor, as he had observed it in the 1890's. During that interval social anthropology, which was in its infancy when Skeat was at work, he passed through major developments of theoretical analysis of field data. But Skeat's book has stood the test of time and has indeed become a classic which has already been reprinted more than once.